Effect of Urea Variation Concentration on Slow Release Fertilizer (SRF) Based Chitosan/NaTPP/Calcium - Wijayanti, Alvia Rachma; Cahyaningrum, Sari Edi (Jurnal Pijar Mipa, 2024)
Environmental pollution due to urea can negatively impact the environment and its surroundings. Efforts to prevent environmental pollution include encapsulating urea made of chitosan/NaTPP/Ca, which aims to determine its physical and chemical properties. This study crosslinks chitosan 1.66%, with NaTPP 3.33%, CaO, with variations in the addition of urea concentrations of 0.05%, 0.1%, 0.15%, 0.2%, and 0.25%. The results of FTIR characterization showed that there were functional groups OH-, C-H, Ca-O, NH, and P=O. The membrane weight yield ranges from 0.14-0.16 grams, while the average membrane thickness is 0.15-0.35 mm. The water absorption test is 1.86-2.64%, and the membrane porosity result is 0.91-2,25%. This shows that the membrane with a base material of 1.66% chitosan and 3.33% NaTPP is the best.